Penalties For Participating In Committing Criminal Acts Of Fraud In Precious Metals Cash On Delivery (Cod) Transactions (Study At The Cibinong State Court) - Mulyana, Riyan Darodjatun; Hartini, Sri; Ferarry, Ande Aditya Iman (JURNAL MAHASISWA YUSTISI, 2025)
Participating in committing criminal acts is a crime that often occurs and has a significant impact against victims and the public, the crime of fraud which is a crime against other people's property is regulated in Article 378 of the Criminal Code. This research aims to understand the criminal procedural law process for participating in committing criminal acts of fraud in Cash On Delivery (COD) transactions and the basis of the judge's considerations in handing down decisions against the perpetrators. This research uses a normative juridical method with a case study approach. Data was obtained through analysis of documents, articles and literature related to this research. Primary data was obtained through the study of court decision documents, while secondary data was obtained from various legal literature. The results of this research show that the Criminal Procedure Law process starts from investigation and investigation, prosecution of the defendant until the court decision. The results of the research also show that this form of participation as the main perpetrator in a criminal act often involves people who have in-depth knowledge of the metal trade. noble, accomplices generally play a role in facilitating transactions, while intermediaries play a role in hiding the proceeds of crime. The application of the law to perpetrators varies, factors that influence the imposition of punishment include the value of the losses experienced by the victim, the level of involvement of the perpetrator, and the presence of an element of planning. This research also found that there is a need to increase legal awareness in the community regarding criminal acts of fraud in Cash On Delivery (COD) transactions of precious metals. This research concludes that criminal acts of fraud in cash on delivery (COD) transactions involving precious metals involve various complex forms of participation.